2016
DOI: 10.18374/ejm-16-1.9
|View full text |Cite
|
Sign up to set email alerts
|

Using Google Trends in Management Fashion Research: A Short Note

Abstract: Google Trends (GT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…First, we will take a look at the awareness and interest in the BOS concept among organizations and managers on the demand-side. The level of awareness provides an indication about the potential adoption and diffusion of a management concept (Madsen 2016a). Therefore, for suppliers of new concepts, it is of critical importance to disseminate information to the adopter market.…”
Section: Awareness and Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we will take a look at the awareness and interest in the BOS concept among organizations and managers on the demand-side. The level of awareness provides an indication about the potential adoption and diffusion of a management concept (Madsen 2016a). Therefore, for suppliers of new concepts, it is of critical importance to disseminate information to the adopter market.…”
Section: Awareness and Interestmentioning
confidence: 99%
“…Another way of assessing managerial interest in BOS is to utilize Internet search data. In previous research it has been suggested that search behavior may say something about the interest in a concept (Madsen 2016a). While Google Trends only contains data from 2004 and onwards, this is not a problem in the case of BOS since the term was not introduced until the mid-2000s Mauborgne 2004, 2005b).…”
Section: Awareness and Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Selv om man bør vaere forsiktig med å tolke for mye ut av data fra Google Trends, kan det gi en indikasjon på trender når det gjelder interessen for og nyhetsverdien til ledelseskonsepter (Madsen, 2016).…”
Section: Interesseunclassified
“…com/trends) (Choi & Varian, 2012) can provide some insights into trends in the interest in management concepts such as outsourcing over a certain time period (Madsen, 2016). A limitation of Google Trends is that it only contains search data from 2004 and onwards, which means that it can only provide a partial picture of the trajectory of the interest in outsourcing.…”
Section: Interestmentioning
confidence: 99%